Pengembangan Ecotourism Taman Nasional Baluran di Kabupaten Situbondo Melalui Edukasi Masyarakat Lokal - Wulandari, Siska Ayu; Rohmah, Alissa Nazilatur (TAAWUN, 2023)
Baluran National Park in Situbondo Regency is very prospective for the development of sustainable tourism that is environmentally friendly and can improve the welfare of local communities. In developing tourism in Baluran National Park there must be community involvement, so the type of tourism that is suitable to be developed is ecotourism. This service aims to increase community participation in the development of Baluran National Park ecotourism through educational outreach and knowing the potential of Baluran National Park. This service activity uses the method of providing educational socialization and a face-to-face approach. The results obtained from this service activity are community enthusiasm in developing ecotourism in Baluran National Park, but it needs to be increased through structured training and community empowerment. The alternative strategy obtained is an ecotourism product development strategy; development of basic and supporting infrastructure and facilities for tourism; tourism market penetration and promotion; security enhancements; as well as institutional and human resource development strategies for tourism. The ecotourism development strategy is a priority strategy to produce ecotourism product development programs and maintain biological natural resources (SDAH).